Early prediction of pregnancy induced hypertension by colour Doppler and role of antioxidants - Singh, Priya; Sharma, Bandana; Singh, Neetu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertension is one of the commonest medical complications during pregnancy and a leading cause of maternal and perinatal mortality. The objective of this study was to evaluate the efficacy of color Doppler in predicting pregnancy induced hypertension at early gestation by assessing blood flow velocity profile and to assess the role of antioxidants in reducing the oxidative stress of the disease by their effect on pregnancy outcome. Methods: The study was carried as a blind prospective study in 310 antenatal patients attending the outpatient department and indoor cases of upper India sugar exchange maternity hospital, GSVM Medical College, Kanpur, Uttar Pradesh, India for a period of 18 months. Results: Early trimester colour Doppler ultrasonography has an excellent role to play as a predictor of pregnancy induced hypertension. However the role of antioxidant supplementation in early pregnancy for amelioration of the process could not be justified. Conclusions: From the above study it is concluded that early trimester colour Doppler ultrasonography has an excellent role to play as a predictor of pregnancy induced hypertension.